Memoria del primer encuentro escénico entre la tradición y la contemporaneidad (2018)
This work of degree gathers the experiences of teachers, students, graduates and specialists in different branches of art and research who attended the First Scenic Encounter between Tradition and Contemporaneity in 2014, a series of steps are carried out to collect and organize the material provided by the Research Seedbed SIEMBRA as the group in charge of the organization. Therefore, a publication is distributed as a result of the report to circulate and deliver to different communities as a sample of the investigative exercises that are carried out within the program of the Performing Arts Degree and some contributions that may be significant for the following versions of the scenic encounter.